Analisis Kompetitif Usaha Kedai Kopi Sebagai Salah Satu Peluang Usaha di Masa Pandemi Covid-19 (Studi Kasus di C’Shalma Coffee Shop) - Darwis Sunandar; Renea Shinta Aminda (Diversity: Jurnal Ilmiah Pascasarjana, 2022)
The COVID-19 pandemic has resulted in many workers being laid off. One of the business opportunities for newly laid off workers with promising prospects is a coffee shop business. The purpose of this research is to find out the right business strategies for newcomers to the coffee shop business. The research method uses SWOT analysis. The results show that the operational strategy suggested in the SWOT Matrix must be based on aggressive growth. According to the IE matrix, the strategy that can be applied by C'Shalma Coffee Shop as a newcomer to the business is an intensive strategy which includes market penetration, market development, and product development. According to QSPM calculations, C'Shalma Coffee Shop must implement a market penetration strategy through price adjustments, increased promotions, product quality improvements, customer referrals, and diversification.